The single market and the geographical diversification of leading firms in the EU - Pavelin, Stephen; Barry, Frank (Economic & Social Studies, 2005)
Geographical diversification describes the degree to which a firm?s operations in a particular industry are dispersed across countries. This paper presents evidence on the geographical diversification within the EU of the roughly 290 largest manufacturing firms in Europe. We explore how geographical diversification changed over the period when the Single Market came into effect, finding that it increased substantially. We also study the variation across sectors and across EU countries. Ireland ? which began its rapid convergence on average EU living standards over this period ? emerges as a special case and receives particular attention.
Keywords: Single market; Geographical diversification; European Union; Ireland; Location of industry